The Palaces of East Prussia (Kaliningrad Region) from the Collection of Alexander Duncker in the Archives of the Herder-Institute in Marburg - Belintseva, Irina V. (Actual Problems of Theory and History of Art, 2018)
Alexander Duncker (1813-1897), the owner of a publishing house and a book trade, published the collection of 959 color lithographs with the images of the best farmstead houses within twelve provinces of Germany in the mid-19th century. The colored engravings, about 16x20 cm in size and framed by a double gold frame, were pasted on cardboard and accompanied by a separate page with the brief information about an estate. Forty-five lithographs were dedicated to the palaces of East Prussia. They became an important document for the history of architecture in the region, as many images of the buildings are now lost. The archival collection of the Herder-Institute in Marburg includes eight original engravings with the images of the palaces of East Prussia which are now within the territory of modern Kaliningrad. Nowadays only the estates in Roshchino (Gryunhof) and Kholmogorowka (Fuchsberg) still exist. They have the status of the objects of cultural heritage. The manor houses in Friedrichshtein and Sanditten, built in the early 18th century for noble families of East Prussia, were among the most luxurious buildings during the era of the heyday of Baroque architecture in Germany. They stood up until the end of the Second World War almost in their intact historic form. A. Duckers’ engravings show us the transformation of buildings in the rise of the estate culture in the 19th century and represent the stylistic samples of the Biedermeier period.